Study of Air Purification System for HVAC Application to Fight Against Virus/ Bacteria to Maintain Indoor Air Quality (IAQ) - Jadhav, Amrut B; Husainy, Avesahemad SN; Mahadik, Shraddha S; Anure, Swarup D; Buchade, Kapil A (Journal of Advanced Research in Mechanical Engineering and Technology, 2021)
The indoor environment is related to the HVAC system and HVAC system is directly related with the respiratory system of human body and for that by focusing the respiratory system, we have to regulate the indoor temperature, humidity, air flow and cleanness. Because they will be the conveyor of microbial contamination, bacteria. In Indoor environment microorganisms that may enter in HVAC system can be generated in many different ways. e.g. People talking, sneezing, carpet and toilet flushing process. And generated, spread by this many ways can survive in various HVAC components such as air ducts, filters, heat exchangers and fan coils. Other HVAC components and metabolism for various bacteria, microorganisms occupy. During the operation of the system bacteria and microorganisms obtain suitable environmental conditions such as temperature, moisture, nutrients conditions for their growth. And when their growth extents, these microorganisms and bacteria diffuse in system in form of bio-aerosols, accumulated dust and spread into indoors with supply air flow. In general, the microbial contamination source of HVAC system, so it is difficult to eliminate the microbial contamination at source. So some methods are able to kill microorganisms by air purification technology. The air purification technology includes different method by which we can maintain the good indoor air quality in HVAC system or applications to fight against the microorganisms, viruses and bacteria. How to cite this article: Husainy ASN, Jadhav AB, Mahadik SS et al. Study of Air Purification System for HVAC Application to Fight against Virus/ Bacteria to Maintain Indoor Air Quality (IAQ). J Adv Res Mech Engi Tech 2021; 8(2): 7-15.